2020
DOI: 10.3390/nu12030714
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Anemia and Micronutrient Deficiencies among Women of Reproductive Age—The Impact of the Wheat Flour Fortification Program in Uzbekistan

Abstract: Food fortification can be effective in reducing the prevalence of anemia and micronutrient deficiencies. This study assessed risk factors for-and the impact of the wheat flour program in Uzbekistan on-anemia, and iron and folate deficiency (FD) in non-pregnant women (NPW) of reproductive age. National data were analyzed for risk factors using multivariable regression. Additional iron intake from fortified flour was not associated with iron deficiency (ID) and did not result in a significantly different prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…We consider our pilot study of the additive effect of smoking and the pre-pregnancy underweight (BMI < 18.5 kg/m 2 ) on risk of hypertension in pregnancy to be extremely important (Table 4 and Table S3). It is possible that the result is associated with deficiencies of many nutrients in underweight people, including microelements and vitamins involved in oxidative balance, and inflammatory or immunological processes [36]. The sizes of the subgroups were small, but we believe that our result requires further research.…”
Section: Discussionmentioning
confidence: 82%
“…We consider our pilot study of the additive effect of smoking and the pre-pregnancy underweight (BMI < 18.5 kg/m 2 ) on risk of hypertension in pregnancy to be extremely important (Table 4 and Table S3). It is possible that the result is associated with deficiencies of many nutrients in underweight people, including microelements and vitamins involved in oxidative balance, and inflammatory or immunological processes [36]. The sizes of the subgroups were small, but we believe that our result requires further research.…”
Section: Discussionmentioning
confidence: 82%
“…Anemia remains a mild public health problem for both preschool children and WRA 51 . A 2017 national survey in Uzbekistan found that one‐third of women consumed additional iron through fortified wheat flour, but this was not associated with reductions in iron deficiency or anemia, likely due to low bioavailability of the fortificant in use at the time 52 . Large‐scale fortification coverage data collected from eight countries between 2013 and 2015 showed variation between and within countries, with more vulnerable households least likely to benefit despite their potential for greater impact in terms of anemia reduction 53 .…”
Section: State Of Multisectoral Strategies and Programs For Anemia Pr...mentioning
confidence: 99%
“…51 A 2017 national survey in Uzbekistan found that one-third of women consumed additional iron through fortified wheat flour, but this was not associated with reductions in iron deficiency or anemia, likely due to low bioavailability of the fortificant in use at the time. 52 Large-scale fortification coverage data collected from eight countries between 2013 and 2015 showed variation between and within countries, with more vulnerable households least likely to benefit despite their potential for greater impact in terms of anemia reduction. 53 Analysis of coverage data from four African countries determined that iron-fortified wheat flour contributed up to 13% of the Recommended Nutrient Intake for WRA, but could be increased to 65% if flour was consistently fortified to standard levels.…”
Section: State Of Multisectoral Strategies and Programs For Anemia Pr...mentioning
confidence: 99%